2001
DOI: 10.1046/j.1365-2141.2001.02728.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet tests in the prediction of myocardial infarction and ischaemic stroke: evidence from the Caerphilly Prospective Study

Abstract: Summary.A platelet test that is predictive of myocardial infarction (MI) and/or stroke would enable the targeting of anti-platelet drugs towards high-risk patients. The predictive power of several platelet tests for MI and for stroke was examined in 2000 older men in the Caerphilly Cohort Study of Heart Disease, Stroke and Cognitive Decline. The tests were: aggregation to adenosine diphosphate (ADP) in platelet-rich plasma (PRP); aggregation to ADP in whole blood measured using an impedance method and a test o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
0
30
1
2
Order By: Relevance
“…The biological significance of our observations remains to be determined. The participation of platelets is crucial in arterial thrombotic events, but ex vivo platelet aggregation tests do not predict risk for future CV events (Elwood et al, 1998(Elwood et al, , 2001. So, the increased wine-related platelet aggregation=secretion reactions detected here do not denote an increased risk of CV events.…”
Section: Beneficial Changes In Haemostasismentioning
confidence: 68%
“…The biological significance of our observations remains to be determined. The participation of platelets is crucial in arterial thrombotic events, but ex vivo platelet aggregation tests do not predict risk for future CV events (Elwood et al, 1998(Elwood et al, , 2001. So, the increased wine-related platelet aggregation=secretion reactions detected here do not denote an increased risk of CV events.…”
Section: Beneficial Changes In Haemostasismentioning
confidence: 68%
“…Evidence on prevalent vascular disease, ischaemic heart disease and/or stroke, including a 12-lead ECG, was recorded. Samples of fasting blood were taken for estimation of platelet (Elwood et al, 2001a), haemostatic (Baker et al, 2002), rheological (Elwood et al, 2001b), lipids (Yarnell et al, 2001), psychosocial (Gallacher et al, 1999) and other factors of possible relevance to vascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…Two small studies have suggested that platelet aggregability assessed by a light transmittance aggregometer could be predictive of cardiovascular events 37,38) ; however, the Northwick Park Heart Study, a large cohort study consisting of 740 men followed up for 10.1 years, found no association of ADP-induced aggregation with ischemic heart disease events 19) . In the Caerphilly Prospective Study, consisting of 2000 elderly men followed up for 10 years, the aggregative response to ADP in platelet- rich plasma, that to ADP in whole blood measured using an impedance method, and platelet aggregation induced in whole blood by high-shear flow did not show an association with myocardial infarction 3) . In this study, we found that the platelet count and platelet aggregation are affected by factors such as gender, age, and lipid levels in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, higher fibrinogen levels were associated with increased epinephrineinduced aggregation and a tendency to word ADPinduced aggregation 8) . Evidence suggests that increased platelet reactivity could identify individuals at risk for atherothrombotic diseases; however, large cohort studies, including the Northwick Park Heart Study and the Caerphilly Prospective Study, did not show an association of platelet aggregability with cardiovascular events 3,19) . Studies on the variability of platelet responsiveness to agonists have been mainly performed in the Caucasian population; studies in the Asian population are very limited.…”
Section: Introductionmentioning
confidence: 99%